2017
DOI: 10.1111/anu.12606
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant-related parameters, digestive enzyme activity and intestinal morphology in rainbow trout (Oncorhynchus mykiss) fry fed graded levels of red seaweed,Gracilaria pygmaea

Abstract: This study was conducted to investigate the effects of dietary red seaweed, Gracilaria pygmaea level on growth, antioxidant-related parameters, digestive enzyme activity and intestinal morphology of rainbow trout (Oncorhynchus mykiss) fry. Five isocaloric and isonitrogenous diets were formulated to contain four G. pygmaea levels (30 (GL-30), 60 (GL-60), 90 (GL-90) and 120 g/kg (GL-120)), and a control diet was used, without inclusion of seaweed. Results of the feeding trial indicated that final body (FBW: 2.8-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 45 publications
4
23
0
Order By: Relevance
“…Two previous studies that assessed the effect of diets supplemented with the brown seaweed, Laminaria digitata , in salmonids found that in Atlantic salmon, food intake and growth performance were not affected [47] while in rainbow trout the final body weight increased, FCR decreased and food intake remained unchanged [48]. More generally, the potential utility of other types of seaweeds as supplements or protein sources for salmonids has been investigated [19,26,49,50]. It was found that the inclusion of up to 10% Porphyra dioica (red seaweed) did not impair growth performance in rainbow trout ( Oncorhynchus mykiss ) but 15% inclusion reduced the final weight of the fish [49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two previous studies that assessed the effect of diets supplemented with the brown seaweed, Laminaria digitata , in salmonids found that in Atlantic salmon, food intake and growth performance were not affected [47] while in rainbow trout the final body weight increased, FCR decreased and food intake remained unchanged [48]. More generally, the potential utility of other types of seaweeds as supplements or protein sources for salmonids has been investigated [19,26,49,50]. It was found that the inclusion of up to 10% Porphyra dioica (red seaweed) did not impair growth performance in rainbow trout ( Oncorhynchus mykiss ) but 15% inclusion reduced the final weight of the fish [49].…”
Section: Discussionmentioning
confidence: 99%
“…The macroalgae product Verdemin (derived from the green seaweed, Ulva ohnoi ) at inclusion levels of 2.5 and 5.0% in juvenile Atlantic salmon diets did not alter feed efficiency and growth performance [19]. Additionally, feeding rainbow trout diets supplemented with Gracilaria pygmaea improved growth performance at 6% inclusion level; however, growth was impaired at 12% inclusion [50]). Further, it was found that the inclusion of 5% Gracilaria vermiculophylla in rainbow trout diet did not negatively impact growth performance but 10% inclusion reduced the final weight, body length, daily growth index and PER [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no adverse effects on growth performance at dietary inclusion levels of 100 g kg −1 for G. bursa‐pastoris and 50 g kg −1 for G. cornea , while 100 g kg −1 of G. cornea reduced growth rate and feed efficiency. Sotoudeh and Mardani fed a Gracilaria pygmaea meal to rainbow trout fry and reported improved growth performance with the inclusion of 60 g kg −1 of G. pygmaea , but reduced final body weight, specific growth rate, and protein efficiency ratio when the inclusion level was increased to 120 g kg −1 . Studies with extruded isoenergetic, isonitrogenous, and isolipidic diets for the European sea bass showed that 75 g kg −1 of Gracilaria spp.…”
Section: Effects On Growth Performance Protein Utilization and Carcamentioning
confidence: 99%
“…at 2.5 or 7.5% levels, or a mix of the three seaweeds (each supplemented at 2.5%) (Peixoto et al 2016). Moreover, Sotoudeh and Mardani (2018) have recently quantified TBARS content in the liver of rainbow trout fry fed diets supplemented with 0, 30 and 60 g/kg of Gracilaria pygmaea, finding that it was not significantly affected by the different diets.…”
Section: Fillet Oxidative Statusmentioning
confidence: 99%